My last tribute to a friend, a pioneer and legend—Dr. David John Sugarbaker (1953–2018) - Yim, Anthony P. C. (Journal of Thoracic Disease; Vol 11, Supplement 14 (September 29, 2019): Journal of Thoracic Disease (The Advanced Lung Disease: Novel Therapies and Controversies Conference), 2018)
On August 29, 2018, the thoracic surgical community throughout the world was shocked by the sad news that a legend suddenly left us. Dr. David John Sugarbaker passed away in Texas after a long battle against liver cancer, something he was keeping very much to his family and close friends until that day.